The Greek Pompeii in Health - Fanourgiakis, John; Kanoupakis, Emmanuel (La Medicina del Lavoro, 2015)
After the official request by Greece’s prime minister for help, the country was put under the supervision of the Troika, that is, European Commission (EC), European Central Bank (ECB) and International Monetary Fund (IMF), and signed with them, in May 2010 the first and in February 2012 the second economic adjustment program, in exchange for financial packages, aiming at helping the country get out of its debt crisis, recover its lost growth and transform the national economy into a more sustainable model, including measures such as reductions in all public expenditures with efficient gains at the same time (1, 2). [...]